2022
DOI: 10.1002/pros.24365
|View full text |Cite
|
Sign up to set email alerts
|

Optimized grade group for reporting prostate cancer grade in systematic and MRI‐targeted biopsies

Abstract: Purpose: To explore an optimized grade group (oGG) criterion from systematic biopsies (SB) and targeted biopsies (TB) and offer a better prediction of radical prostatectomy (RP) grade group (GG).Methods: Positive needles were collected from 146 patients who underwent SB + TB followed by RP. The grade was assigned for two different kinds of biopsies with five GG criteria: (1) global GG (gGG); (2) most common GG (most common GG from SB + TB, mGG); (3) highest GG (highest numerical GG from SB + TB, hGG); (4) larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In addition, a recent study has demonstrated that the gGG combining all positive targeted and standard biopsy cores resulted in a suboptimal concordance rate (47.2%) with the RPGG. 22 While standard and targeted biopsies may often be performed in conjunction, our results support the current guidelines to report the grade of the targeted and standard cores separately. By focusing on a highly selective cohort of MRI-targeted prostate biopsies where gGG ≠ hGG, we illustrated the advantages and limitations of each biopsy grading method and circumstances where one method may be preferentially used over the other.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, a recent study has demonstrated that the gGG combining all positive targeted and standard biopsy cores resulted in a suboptimal concordance rate (47.2%) with the RPGG. 22 While standard and targeted biopsies may often be performed in conjunction, our results support the current guidelines to report the grade of the targeted and standard cores separately. By focusing on a highly selective cohort of MRI-targeted prostate biopsies where gGG ≠ hGG, we illustrated the advantages and limitations of each biopsy grading method and circumstances where one method may be preferentially used over the other.…”
Section: Discussionsupporting
confidence: 78%
“…The high proportion of targeted lesions with gGG = hGG likely masked the power of either biopsy method to predict the RPGG independently. In addition, a recent study has demonstrated that the gGG combining all positive targeted and standard biopsy cores resulted in a suboptimal concordance rate (47.2%) with the RPGG 22 . While standard and targeted biopsies may often be performed in conjunction, our results support the current guidelines to report the grade of the targeted and standard cores separately.…”
Section: Discussionsupporting
confidence: 50%
“…This diagnostic pathway is commonly used to assess PCa prognosis. Multiple follow-up appointments are recommended, especially for men under active surveillance [47][48][49][50] .Notably, over 77% of men with localized PCa are suitable for active surveillance, and this number has increased from 15.5% to 42.2% over the last decade. These men require repeat follow-ups every six months or 1 year if enrolled 51-53 .…”
mentioning
confidence: 99%
“…Positive results on these assays may prompt imaging studies, such as MRI, to identify potential areas of PCa [40][41][42][43][44][45] . Clinicians may also perform biopsies for further evaluation by pathologists and genomic testing [46][47][48][49][50] . This diagnostic pathway is commonly used to assess PCa prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation